"Dad Doesn't Text": Examining How Parents' Use of Information Communication Technologies Influences Satisfaction Among Emerging Adult Children. (December 2014) - Schon, Jennifer
Advancements in technology have altered how and when communication occurs between individuals in a relationship. Although research has investigated how new information communication technologies (ICTs) affect peer relationships and parents' communication with their young children, how ICTs influence parent–adult child relationships is less clear. Based on media multiplexity theory (MMT), this study tested whether the number of media used to interact influences communication and relationship satisfaction for emerging adult children. Results indicated that the number of media parents and emerging adult children utilize to maintain their relationship does modestly influence communication and relationship satisfaction. Furthermore, these results imply that utilizing additional media can offset a parent's low communication competence. These findings extend MMT to family relationships and underscore the importance of communication competence in communication and relationship satisfaction.